The direction of shift-work rotation impacts metabolic risk independent of chronotype and social jetlag – An exploratory pilot study. (December 2014) - Kantermann, Thomas; Duboutay, Françoise; Haubruge, Damien; Hampton, Shelagh; Darling, Andrea L.; Berry, Jacqueline L.; Kerkhofs, Myriam; Boudjeltia, Karim Zouaoui; Skene, Debra J.
<x xml:space="preserve">Abstract</x> The aim of this pilot study was to explore the risk of metabolic abnormalities in steel workers employed in different shift-work rotations. Male workers in a steel factory [16 employed in a fast clockwise rotation (CW), 18 in slow counterclockwise rotation (CC), 9 day workers (DW); mean age 43.3 ± SD 6.8 years] with at least 5 years experience in their current work schedule participated. All workers provided fasting blood samples between 06:00 and 08:00 h for plasma glucose, insulin, apo-lipoproteins A and B (ApoA, ApoB), high- and low-density lipoproteins (HDL and LDL), total cholesterol (tCH), triglycerides (TG), minimally oxidized (mox) LDL, C-reactive protein (CRP), interleukin-8 (IL-8) and serum 25-hydroxyvitamin D (25(OH)D). HOMA index (homeostatic model assessment) was calculated to evaluate insulin resistance, beta cell function and risk of diabetes. Information on demographics, health, stimulants, sleep, social and work life, chronotype (phase of entrainment) and social jetlag (difference between mid-sleep on workdays and free days) as a surrogate for circadian disruption was collected by questionnaire. Neither chronotype nor social jetlag was associated with any of the metabolic risk blood markers. There were no significant differences in 25(OH)D, ApoA, ApoB, CRP, HDL, IL-8, insulin, LDL, mox-LDL, mox-LDL/ApoB ratio, tCH and TG levels between the three work groups. Although we did observe absolute differences in some of these markers, the small sample size of our study population might prevent these differences being statistically significant. Fasting glucose and HOMA index were significantly lower in CW compared to DW and CC, indicating lower metabolic risk. Reasons for the lower fasting glucose and HOMA index in CW workers remains to be clarified. Future studies of workers in different shift rotations are warranted to understand better the differential effects of shift-work on individual workers and their health indices.